Influence of circular permutations on the structure and stability of a six‐fold circular symmetric designer protein. (16th October 2020) - Mylemans, Bram; Noguchi, Hiroki; Deridder, Els; Lescrinier, Eveline; Tame, Jeremy R. H.; Voet, Arnout R. D.
Abstract: The β‐propeller fold is adopted by a sequentially diverse family of repeat proteins with apparent rotational symmetry. While the structure is mostly stabilized by hydrophobic interactions, an additional stabilization is provided by hydrogen bonds between the N‐and C‐termini, which are almost invariably part of the same β‐sheet. This feature is often referred to as the "Velcro" closure. The positioning of the termini within a blade is variable and depends on the protein family. In order to investigate the influence of this location on protein structure, folding and stability, we created different circular permutants, and a circularized version, of the designer propeller protein named Pizza. This protein is perfectly symmetrical, possessing six identical repeats. While all mutants adopt the same structure, the proteins lacking the "Velcro" closure were found to be significantly less resistant to thermal and chemical denaturation. This could explain why such proteins are rarely observed in nature. Interestingly the most common "Velcro" configuration for this protein family was not the most stable among the Pizza variants tested. The circularized version shows dramatically improved stability, which could have implications for future applications. Abstract : PDB Code(s): 6I37, 6I38, 6I39, 6I3A and 6I3B ;